Surface Treatment of Superabsorbent Polymer with Corn Starch for Improved Properties - Malendres, Ariel V.; Carrillo, Lorraine A (ASEAN Journal of Chemical Engineering, 2019)
Samples of superabsorbent polymer (SAP) were treated with corn starch to modify absorption and permeability properties. The process was done by homogenously mixing the superabsorbent polymer particles with starch suspension using starch loading of 0.002-0.20 g of starch per g of SAP. The resulting mixture was then dried at temperature of 150oC. The absorption properties such as Free Swell Capacity (FSC) and Absorption Under Pressure (AUP) of treated SAP were determined at different starch loading using test solution of varying sodium chloride concentrations and compared with the untreated SAP. At starch loading of 0.04 g/g, AUP gave better results than untreated SAP. GLP of treated SAP gave significant improvement which is explained in terms of the controlled swelling of SAP particles and a more porous structure of the SAP gel layer that allows faster liquid flow rate.